Improving learning outcomes through problem-based learning: A literature review - Noor Hidayah Pratami; Aminuddin Prahatama Putra; Yudi Firmanul Arifin (HAFECS PRESS, 2024)
As the times change, science and technology also change, and the educational system must adapt to these developments. Among them is the need that students possess the six Cs of 21st-century skills: communication, character, citizenship, critical thinking, and creativity. Critical thinking abilities for problem-solving are the abilities being developed at the moment. Students are supposed to be able to handle difficulties in their everyday lives using these abilities, which will eventually affect their learning results. Since many instructors still employ teacher-centered learning in the real world, pupils' critical thinking skills are underdeveloped. Problem-based learning is one kind of instruction that may be utilized to enhance critical thinking abilities. This research described how problem-based learning affects student learning outcomes using a systematic literature review that used the PRISMA diagram. Searching for